2019
DOI: 10.12659/ajcr.918403
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Small Bowel Obstruction Due to Paraduodenal Hernia

Abstract: Patient: Female, 24Final Diagnosis: Paraduodenal herniaSymptoms: Abdominal pain • Bowel obstructionMedication: —Clinical Procedure: Surgical excision of the sac and release of adhesionSpecialty: SurgeryObjective:Challenging differential diagnosisBackground:Paraduodenal hernia, or mesocolic hernia, is a rare congenital form of internal abdominal hernia, and is classified into right and left, with left paraduodenal hernia being more common than right. Patients can have non-specific symptoms and signs, which make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Satapara et al and Al Otaibi et al reported LPDH in young female patients. 6,7 Kozman and Fisher reported a case of LPDH postlaparoscopic appendectomy in a 15-yearold female patient. 8 We report a case of LPDH in an atypical patient profile, that is, young and female.…”
Section: Discussionmentioning
confidence: 99%
“…Satapara et al and Al Otaibi et al reported LPDH in young female patients. 6,7 Kozman and Fisher reported a case of LPDH postlaparoscopic appendectomy in a 15-yearold female patient. 8 We report a case of LPDH in an atypical patient profile, that is, young and female.…”
Section: Discussionmentioning
confidence: 99%
“…Para-duodenal hernia is dened as abnormal protrusion of viscera into the para-duodenal fossa and results in less than 1% of all cases of small intestinal obstruction [1].…”
Section: Discussionmentioning
confidence: 99%
“…Left PDH [75%] is commoner than right PDH [25%] [1].Embryological development of right para-duodenal hernia consists of non-rotation of pre-arterial segment of midgut [2], whereas development of left PDH consists of normal rotation of gut but abnormal xation of the descending mesocolon to the posterior abdominal wall, which leads to formation of an unsupported area[Landzert's fossa] and herniation of contents into it. This lies lateral to the fourth part of the duodenum, posterior to the inferior mesenteric vein [IMV], the ascending branch of the left colic artery [LCA] and anterior to posterior parietal peritoneum [2].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal obstruction is a common clinical condition encountered in emergency rooms around the world. Internal herniae figure among it's rare causes and account for just about 1–2% of all cases [1] . Internal herniae are protrusions of the viscera through defects in the mesentery or peritoneum, contained within the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…Internal herniae are protrusions of the viscera through defects in the mesentery or peritoneum, contained within the abdomen. Broad ligament hernia (BLH) is a rare type of internal hernia and accounts for just 4% of all internal hernias [1] . It is difficult to diagnose due to it's vague symptomatology [2] .…”
Section: Introductionmentioning
confidence: 99%